2018
DOI: 10.1007/s12603-017-0984-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Uric Acid Level and Carotid Atherosclerosis in Chinese Individuals Aged 75 Years or Older: A Hospital-Based Case-Control Study

Abstract: The elevated serum uric acid level may be independently and significantly associated with the presence and progression of carotid atherosclerosis in Chinese individuals aged 75 years or older.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“… 9 Increased SUA was associated with the development and progression of atherosclerosis. 10 However, the researches focused on the relationship between SUA and SA was still absent. Furthermore, studies have shown that menopausal women are more likely to develop atherosclerosis, especially prominent in late postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Increased SUA was associated with the development and progression of atherosclerosis. 10 However, the researches focused on the relationship between SUA and SA was still absent. Furthermore, studies have shown that menopausal women are more likely to develop atherosclerosis, especially prominent in late postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%